2010
DOI: 10.1111/j.2042-3306.2010.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevating the uterus (uteropexy) of five mares by laparoscopically imbricating the mesometrium

Abstract: Elevating a ventrally-angled uterus to a horizontal position may improve egress of uterine debris, thereby improving fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
1
15
0
2
Order By: Relevance
“…Failure to accomplish repair through the midline approach would necessitate a planned repair through a different approach later, such as a standing flank laparoscopy with intracorporeal suture closure of the defect (Brink et al . ). This would be similar to the standing laparoscopic repair of a mesoduodenal rent in a broodmare performed 2 days after correction of small intestinal incarceration through it (Sutter and Hardy ).…”
Section: Discussionmentioning
confidence: 97%
“…Failure to accomplish repair through the midline approach would necessitate a planned repair through a different approach later, such as a standing flank laparoscopy with intracorporeal suture closure of the defect (Brink et al . ). This would be similar to the standing laparoscopic repair of a mesoduodenal rent in a broodmare performed 2 days after correction of small intestinal incarceration through it (Sutter and Hardy ).…”
Section: Discussionmentioning
confidence: 97%
“…Another report evaluated laparoscopic techniques for investigating the equine oviduct [100]. Brink et al [101] reported on the use of laparoscopy for raising the uterus in multiparous mares that were not rebreeding. In 5 mares, the broad ligament was “shortened” by use of laparoscopic suturing.…”
Section: Surgery Of the Female Reproductive Tractmentioning
confidence: 99%
“…The most common include ovariectomy, cryptorchidectomy, inguinal herniorrhaphy, bladder repair and removal of cystic calculi (Edwards et al 1995;Davis 1997;Hanson and Galuppo 1999;Marien 2001;Rocken et al 2006). Others include adhesiolysis, nephrosplenic space obliteration, umbilical remnant resection, diaphragmatic hernia repair, colopexy and uteropexy (Bleyaert et al 1997;Trostle et al 1998;Fischer 1999;Malone et al 2001;Marien et al 2001;Brink et al 2010). These surgeries are considered to be minimally invasive as surgical time, tissue trauma, incisional complications, incision size and convalescence are reduced with experienced surgeons (Klohnen 2002).…”
Section: Introductionmentioning
confidence: 99%